Cognitive antihyperlipidemic and antioxidant activities of bitter leaf (Vernonia amygdalina) and Scent leaf (Ocimum gratissimum) - Ibukun Emmanuel Oluwafemi,; Onunkwor Okechukwu Beno,; Babalola Oluwafemi Akanji,; Gideon Oludare Oladipo,; Nlekerem Chidinma Martha,; Durojaiye Oluwafemi, (International Journal of Phytomedicine, 2016)
Oxidative stress manifests an imbalance in the production and the detoxification of free radicals. Free radicals cause oxidative degradation of biomolecules like lipids, proteins, nucleic acids, and carbohydrate molecules, thereby compromising cell integrity and function and leading to health deterioration from a range of metabolic anomalies that cause diseases and ailments including cardiovascular diseases (CVD), hypertension, stroke and cancer. Both bitter leaf (VA) and Scent leaf (OG) have been medicinally useful in the cure of diseases in different cultures.The addition of scent leaf as additive in preparation of delicacies in Nigeria has prompted this study to determine the cognitive activities of both plants to repair the damages caused by high fat diet present, by evaluating the antidyslipidemic activitiesas well as their antioxidant potentials. The results obtained revealed that both plants have antioxidant abilities when subjected to standard antioxidant evaluations although VA was significantly higher (p˂0.05) when compared with OG, however the cognitive effects showed that the antioxidant potentials of VA was depressed on the addition of OG. The results obtained from the modulation of lipid in albino rats challenged with hyperlipidemia showed that both VA and OG have a positive effect to lower LDL-C, TAG, TCHOL and increase HDL-C thus potentiating their antidyslipidemic ability and protective role against dyslipidemic disorders. Similarly, the cognitive effect showed reduction in the activities of VA while the activity of OG was boosted. The high phospholipid contents of the selected tissues upon treatments with the leaf extracts also showed that both VA and OG can have ameliorating effects on coronary heart disease, inflammation or cancer by enhancing membrane integrity. It is noteworthy that both VA and OG have good potential in the ability to reverse induced dyslipidemia and in spontaneous cellular lipid, while the addition causes a reduction in the activities of VA.